How fast did T. rex run? : unsolved questions from the frontiers of dinosaur science - Hone, David (Princeton University Press, 2022)
"In just the past twenty years, we have learned more about dinosaurs than we did in the previous two centuries. This book describes the extraordinary advances in paleontology that are beginning to solve many of the mysteries surrounding these marvelous prehistoric creatures, from their ways of communicating to their mating habits, the color of their skin, their migration patterns and extinction. How did dinosaurs rear their young? What did they eat? What did T. rex actually do with those tiny arms? David Hone draws on his own discoveries at the forefront of dinosaur science to illuminate these and other questions. Each chapter in this lively and informative book covers a key topic in dinosaur science, such as origins, diversity, evolution, habitats, anatomy, behavior, ecology and dinosaur descendants--the birds. For each topic, Hone discusses the history of what paleontologists thought in the past, the new insights we are gleaning from recent fossil finds and the latest technologies and the gaps in our knowledge that still remain. He shares his own predictions about the research areas that may produce the next big ideas in dinosaur science and addresses the unknowns we may never solve. How Fast Did T. rex Run? reveals everything we now know about dinosaurs--and everything we don't--and charts thrilling new directions for tomorrow's generation of dinosaur scientists"--